AUTISM AND AUTISM SPECTRUM DISORDERS (ASD) DIAGNOSIS AND PREVENTION IN CHILDREN - Kozirakhimova Nargiz Kodirjonovna; Turgunov Shukhratillo Khasanovich (Bright Mind Publishing, 2025)
This article revisits childhood autism, its impact on the body and physiological functions, and the fight against this disease. It analyzes recent publications on childhood autism, pediatric interventions, and preventive methods, as well as highlights issues and recommendations for future research and practical application.
Keywords: Autism, Autism Spectrum Disorders (ASD), empathy.